Impact of Small-Scaled Differences in Micro-Aggregation on Physico-Chemical Parameters of Macroscopic Biopore Walls - Haas, Christoph; Horn, Rainer (Frontiers in Environmental Science, 2018)
Macroscopic biopores, like earthworm burrows or channels which remain after a root decayed, act as preferential flow paths for water, gas, and heat transport processes, and viewing at agricultural production, as preferential elongation paths for plant roots. These processes result in intense alterations of the soil volume and its composition that surrounds the pores. The effects of these processes were analyzed at small-scale and physico-chemical soil parameters, i.e., relative oxygen diffusion coefficient (Ds/DO), oxygen partial pressure pO2, Eh and pH of biopore walls, were measured. The analyses were carried out on undisturbed soil samples with different colonization history, excavated from a haplic Luvisol derived from loess. Soil resistance to penetration was determined simultaneously with Ds/DO and pO2 using a coupled, self-developed approach, and four matric potentials (namely, Ψm = −1 kPa; −3 kPa; −6 kPa or −30 kPa) were considered. We hypothesized that physico-chemical soil parameters in biopore walls were altered due to differing influences on the soil aggregation. Aggregation was visualized with scanning electron microscopy, classified and used to explain differences in–soil properties. Plant roots and earthworms altered aggregation next to biopore surfaces in a contrasted way, either by enhancing aggregates diversity or homogenizing it. Roots led to the formation of subpolyeders while earthworms formed subplates. Pore functions of microaggregates were comparable to those of larger scale, and subpolyeders showed much more favorable soil properties in terms of soil aeration (Ds/Do, pO2). Replicates of all parameters scattered intensely and showed deviations up to several orders of magnitude in case of Ds/DO underlining the large variability of soil properties in biopore walls.